Sclerosing encapsulating peritonitis: a rare case presenting as intestinal obstruction - Padhy, Aditya Prasad; Dash, Swetamayee (International Surgery Journal, 2019)
Abdominal cocoon or sclerosing encapsulating peritonitis is a rare condition of unknown/ multifactorial etiology in which intestinal obstruction result from encasement of variable length of bowel by dense fibro collagenous membrane. A young adolescent girl reported with features of small bowel obstruction for more than one year. CT scan suggested features of internal obstruction. On exploration, she was found to have all viscous densely covered with a thick white gelatinous like membrane. The membrane was gently peeled off from the bowel. The patient recovered well and was discharged on an oral diet. Preoperative diagnosis of sclerosing encapsulating peritonitis is difficult and incidentally it is discovered on laparotomy. CECT is helpful in preoperative diagnosis. Main stay of treatment for this is surgery. Simple removal of the membrane after lysis of the adhesions produces optimal outcome. When the intestine is nonviable, bowel resection should be done. A high index of suspicion and appropriate radiology can prevent ‘surprises’ on laparotomy and unnecessary bowel resection. Simple removal of the membrane gives a good outcome.